Perancangan Media Pembelajaran Taat Berlalu Lintas Dengan Teknologi Augmented Reality Berbasis Android: (Studi : TK Aisyiyah Malangjiwan Colomadu) - Ponco Purnaning Raharjo; Riyan Abdul Aziz; Hadis Turmudi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The research is aimed at research development pengembangkan media learning rambu-rambu traffic aumented reality based, the media learning traffic signals using modeling 3 dimensions.This study using methods prototyping.. The results of the plan are obtained by the media learning of the traffic tracks consisting of eight main menus: stop, Take care of the smooth road, It is forbidden to turn right. The left is forbidden. Parking is forbidden. The green light, Yellow lights and red lights on paud / tk students let the introduction of traffic bars with user response very well proven with a score of 90,5% respondents agree if this application is very helpful as a cross-counter obedient identification tool.Augmented Reality Traffic-based media app can display Objects.